Association of pro-inflammatory high-density lipoprotein cholesterol with clinical and laboratory variables in sickle cell disease. Issue 5 (June 2015) - Ataga, Kenneth I.; Hinderliter, Alan; Brittain, Julia E.; Jones, Susan; Xu, Hao; Cai, Jianwen; Kim, Soyoung; Pritchard, Kirkwood A.; Hillery, Cheryl A.
<x content-type="archive" xml:space="preserve">Abstract</x> Background Although cholesterol levels are known to be decreased in sickle cell disease (SCD), the level of pro-inflammatory high-density lipoprotein cholesterol (proHDL) and its association with clinical complications and laboratory variables has not been evaluated. Design and methods Plasma levels of total cholesterol, high-density lipoprotein cholesterol (HDL), proHDL, and selected clinical and laboratory variables were ascertained in a cohort of SCD patients and healthy African American control subjects in this single-center, cross-sectional study. Results Although total cholesterol was significantly lower in SCD patients compared with control subjects, HDL and proHDL levels were similar in both the SCD and control groups. In univariate analyses, proHDL was correlated with echocardiography-derived tricuspid regurgitant jet velocity. ProHDL was higher in SCD patients with suspected pulmonary hypertension (PHT) compared to patients without suspected PHT. ProHDL was positively correlated with lactate dehydrogenase, total bilirubin, direct bilirubin, indirect bilirubin, prothrombin fragment 1+2, D-dimer, and thrombin–antithrombin complexes. In multivariable analyses, only higher lactate dehydrogenase and direct bilirubin levels were associated with higher levels of proHDL. Conclusions SCD is characterized by hypocholesterolemia. Although proHDL is not increased in SCD patients compared with healthy controls, it is significantly associated with markers of liver disease. In addition, proHDL is associated with tricuspid regurgitant jet velocity and markers of coagulation, although these associations are not significant in multivariable analyses.